Anthropometric assessment in children with congenital heart disease - Rubia, Begam; Kher, Anjali (International Journal of Contemporary Pediatrics, 2018)
Background: Congenital Heart Diseases (CHD) are often associated with malnutrition with prevalence of 64%. Malnutrition in CHD increases morbidity and mortality in these children and hence it is essential to assess the nutritional status of the children with CHD so that proper nutritional therapy and rehabilitation can be done. Methods: In this case control study 126 cases of un operated CHD in the age group of >28 days to 10 years and 126 age and gender matched controls without CHD were studied during a period of 2 year. Informed consent from the parents was obtained and they were interviewed using pre-validated proforma and relevant clinical examination, detailed anthropometric assessment was done of all cases and control. Results: Male to female ratio was 0.9:1. Maximum cases were in age group of 1 to 5 years. Acyanotic CHD was seen in 80.16% and cyanotic CHD was seen in 19.84%. Stunting was seen in 58.72% cases and in 41.26% of controls. 82.53% of cases and 24.6% of controls were underweight. Conclusions: The prevalence of acyanotic CHD was more common than cyanotic CHD. In acyanotic CHD cases VSD was commonest and in cyanotic CHD cases TOF was the commonest lesion. The overall prevalence of underweight and stunting was high in cases than controls. In acyanotic CHD underweight and stunting was high than cyanotic CHD. In this study malnutrition correlated significantly with congestive heart failure, low hemoglobin level, poor dietary history and pulmonary hypertension and this was statistically highly significant.